Factors Influencing Customer Satisfaction and Their Impact on Customer Loyalty - Septiano, Renil; Defit, Sarjon; Yulasmi, Yulasmi; Limakrisna, Nandan; Lusiana, Lusiana (Universitas Dharma Wacana, 2024)
Workshop customers, known as unit entry by the automotive world, are one of the sources of revenue for automotive companies. Workshop unit entry is related to customer loyalty. The study aims to determine the relationship between perceived price on customer loyalty through customer satisfaction in auto repair shops customers. A quantitative approach is used as a research approach. Data were collected by questionnaire. The collected data were analyzed to determine the effect between variables, and the analysis technique was Partial Least Square (PLS). The research was conducted at Auto2000 West Sumatra. The research subjects are Auto2000 consumers who use workshop services. The object of research is a review of the influence of perceived price on customer loyalty with customer satisfaction as mediation. The sampling technique is purposive sampling. The results showed that Customer satisfaction can mediate the effect of perceived price on customer loyalty of consumers who use Auto2000 workshop services.